Combining Protein Expression and Molecular Data Improves Mutation Characterization of Dystrophinopathies - Gaina, Gisela; Vossen, Rolf H. A. M.; Manole, Emilia; Plesca, Doina Anca; Ionica, Elena (Frontiers in Neurology, 2021)
Duchenne and Becker muscular dystrophy are X-linked recessive inherited disorders characterized by progressive weakness. Different mutations in the DMD gene, which encodes for dystrophin protein, are responsible for these disorders. The aim of our study was to investigate the relationship between type, size, and location of the mutation that occurs in the DMD gene and their effect on dystrophin protein expression in a cohort of 40 male dystrophinopathy patients and nine females, possible carriers. We evaluated the expression of dystrophin by immunofluorescence and immunoblotting. The mutational spectrum of the DMD gene was established by MLPA for large copy number variants, followed by HRM analysis for point mutations and sequencing of samples with an abnormal melting profile. MLPA revealed 30 deletions (75%) and three duplications (7.5 %). HRM analysis accounted for seven-point mutations (17.5%). We also report four novel small mutations (c. 8507G>T, c.3021delG, c.9563_9563+1ins20bp, c.7661-60T>A) associated with DMD phenotype. Our work shows that the DNA translational open reading frame and the location of the mutation both influence the expression of dystrophin and disease severity phenotype. The proposed algorithm used in this study demonstrates its accuracy for the characterization of dystrophinopathy patients.